2015
DOI: 10.1007/s12640-015-9552-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid-Beta Levels are Increased in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is associated with cognitive decline, but the molecular link between COPD and dementia or Alzheimer's disease (AD) remains unclear. This study was aimed to investigate whether serum Aβ levels are correlated with COPD. 77 cognitively normal COPD patients and 45 age- and gender-matched normal controls were admitted to the study. Serum Aβ40 and Aβ42 levels were measured using ELISA kits. Serum C-reactive protein (CRP), interleukin 6 (IL-6), and procalcitonin (PCT) meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 32 publications
1
10
1
Order By: Relevance
“…COPD and AD are thought to share several mechanisms of neuronal damage [28]. Our previous study suggested that COPD is associated with higher plasma levels of amyloid-beta (an AD biomarker) and inflammatory cytokines [29], which are closely associated with AD [7]. In this study, chronic pulmonary disease (mostly COPD) occurred more frequently in AD patients than VaD patients.…”
Section: Discussionmentioning
confidence: 51%
“…COPD and AD are thought to share several mechanisms of neuronal damage [28]. Our previous study suggested that COPD is associated with higher plasma levels of amyloid-beta (an AD biomarker) and inflammatory cytokines [29], which are closely associated with AD [7]. In this study, chronic pulmonary disease (mostly COPD) occurred more frequently in AD patients than VaD patients.…”
Section: Discussionmentioning
confidence: 51%
“…A broader impact of pulmonary inflammation on neurologic outcomes is implied by our findings, which may explain more generally the comorbid associations between lung disease and cognition deficits and neurodegenerative diseases (53,54). A loss of BBB integrity caused by circulating factors of pulmonary origin may be central to the neurologic outcomes of pulmonary inflammation, remodeling, or toxicity owing to inhaled toxicants.…”
Section: Discussionmentioning
confidence: 60%
“…Compared with healthy control individuals, patients with OSA or chronic obstructive pulmonary disease exhibit higher blood levels of Aβ, which negatively correlate with pulmonary function 121,122 . OSA is also associated with altered levels of AD biomarkers in CSF, including decreased levels of Aβ 42 and elevated levels of phosphorylated tau 123 .…”
Section: Respiratory and Sleep Disordersmentioning
confidence: 99%